Portable point-of-care diagnostic devices: an updated review. Issue 45 (17th November 2021) - Shu, Tong; Hunter, Haley; Zhou, Ziping; Sun, Yanping; Cheng, Xiaojun; Ma, Jianxin; Su, Lei; Zhang, Xueji; Serpe, Michael J.
Abstract : This review highlights recent examples of point-of-care (POC) diagnostics for detecting nucleic acids, proteins, bacteria, and other biomarkers, all focused on highlighting the positive impact of POC on society and human health. Abstract : The global pandemic caused by the SARS-CoV-2 (COVID) virus indiscriminately impacted people worldwide with unquantifiable and severe impacts on all aspects of our lives, regardless of socioeconomic status. The pandemic brought to light the very real possibility of pathogens changing and shaping the way we live, and our lack of preparedness to deal with viral/bacterial outbreaks. Importantly, the quick detection of pathogens can help prevent and control the spread of disease, making the importance of diagnostic techniques undeniable. Point-of-care diagnostics started as a supplement to standard lab-based diagnostics, and are gradually becoming mainstream. Because of this, and their importance in detecting pathogens (especially in the developing world), their development has accelerated at an unprecedented rate. In this review, we highlight some important and recent examples of point-of-care diagnostics for detecting nucleic acids, proteins, bacteria, and other biomarkers, with the intent of making apparent their positive impact on society and human health.